Thieves' road : the Black Hills betrayal and Custer's path to Little Bighorn - Mort, T. A. (Terry A.) (Prometheus Books, 2015)
Tells the little-known story of this exploratory mission and reveals how it set the stage for the climactic Battle of the Little Bighorn two years later. What is the significance of this obscure foray into the Black Hills? The short answer, as the author explains, is that Custer found gold. This discovery in the context of the worst economic depression the country had yet experienced spurred a gold rush that brought hordes of white prospectors to the Sioux's sacred grounds. The result was the trampling of an 1868 treaty that had granted the Black Hills to the Sioux and their inevitable retaliation against the white invasion.